Antiulcerogenic effect of Capparis cartillaginea decne on indomethacin induced gastric ulcer in wistar rats - Mugo, Nancy W.; Wangia, Christine; Kikuvi, Gideon; Ngugi, Samuel (International Journal of Research in Medical Sciences, 2020)
Background: Peptic ulcer disease is a non-malignant, mucosal lesion of the stomach or duodenum. The mucosal defect reaches the muscularis mucosa and sometimes, beyond causing life threatening complications, including haemorrhage, perforations, gastrointestinal obstruction and malignancy. Methods: The animals were pre-treated with omeprazole 20 mg/kg and 300 mg/kg of Capparis cartillaginea decne orally for 14 days. On the 15th day, ulcers were induced using indomethacin 30 mg/kg and 4 hours post ulcer induction, they were sacrificed. Ulcer index, pH, total acidity and volume were determined. Results: Extensive lesions were seen in indomethacin ulcerated rats with mean ulcer score of (1.260±0.18). In comparison, there were minimal areas of erosion on animals pre-treated with omeprazole (0.14±0.025) and plant extracts (0.280±0.097). Indomethacin-induced ulcer treated animals showed the highest volume of gastric juice output (3.14±0.21 ml), whereas the animals pre-treated with omeprazole had lower gastric juice output (2.20±0.2 9ml). This was comparable to animals pre-treated with the plant extract (1.80±0.13 ml). The pH was high in animals pre-treated with omeprazole (5.02±0.53). This was also seen in animals pre-treated with the extract (4.82±0.31). This was in comparison to the low pH seen in indomethacin ulcerated animals (2.20±0.16). Indomethacin-induced ulcer treated animals showed high levels of total acidity (88.64±1.71 mEq/L). Whereas the animals pre-treated with omeprazole had lower total acidity (55.26±3.77 mEq/L), which was also mirrored in animals pre-treated with the plant extracts (61.44±2.42 mEq/L). Conclusions: The extracts of Capparis cartillaginea decne showed anti-ulcer effect on indomethacin induced ulcers in Wistar rats.